Tick-borne haemoparasite prevalence and Theileria parva strain diversity in African buffalo (Syncerus caffer) from northern Botswana and Gonarezhou National Park, Zimbabwe - Oosthuizen, Marinda C. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.